From Georgy Adamovich Papers - Andrey Serkov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The work is devoted to the publication of archival materials related to the poet and literary critic Georgy Adamovich (1892–1972) and not included in his Collected Works, the publication of which has begun not long ago. The published selection, which makes a certain contribution to the study of the poet’s heritage and literature of the Russian Diaspora, is called upon to present different aspects of Adamovich’s activity. The first block is devoted to his Masonic activity and includes one of the reports read by Adamovich at a meeting of Russian Masonic lodges in Paris, “The Secret of Pushkin”. The second part of the selection, demonstrating the diversity of Adamovich’s correspondence, is presented by a letter from the poet Alla Golovina concerning the last days of her brother Anatoly Shteiger, also the poet, probably the most prominent representative of the so-called “Paris note”. The letter is addressed to Adamovich as an ideologist of the indicated literary direction. As an example of materials for an unpublished volume of Adamovich’s Collected Works, his speech at the evening dedicated to Teffi (Nadezhda Aleksandrovna Lokhvitskaya-Buchinskaya, 1872 −1952) is selected. Materials are accompanied by an introductory note and publisher’s comments.